1996
DOI: 10.1007/bf02556295
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the cold pressor test: studies in normal subjects

Abstract: The reproducibility of the cold pressor test was studied in healthy subjects. A non-invasive method was utilized for estimating beat-to-beat arterial blood pressure (BP) and heart rate (HR). The study population of 17 healthy volunteers consisted of two groups. In the first group (Group 1, n = 11), a 1-min test was performed three times during the same day. In the second group (Group 2, n = 6), a 2-min test was repeated at the same time of the day on three consecutive days. In both groups, the test response wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Moreover, even if CPT is a wide used test to increase sympathetic nervous activity this test presents indeed a large intraindividual variability (reliability) and a limited reproducibility. [42,43] In summary our study provides evidence for the presence of PB in a considerable number of hypertensive patients. PB was associated with greatly enhanced responses to cold pressor testing, indicating a potentiation of sympathetic outflow.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, even if CPT is a wide used test to increase sympathetic nervous activity this test presents indeed a large intraindividual variability (reliability) and a limited reproducibility. [42,43] In summary our study provides evidence for the presence of PB in a considerable number of hypertensive patients. PB was associated with greatly enhanced responses to cold pressor testing, indicating a potentiation of sympathetic outflow.…”
Section: Discussionsupporting
confidence: 53%
“…four minutes. The cold-pressor test has been extensively used in laboratory settings to elicit a stress response [33], [34], [35], [36]. It has been demonstrated that adding a social evaluative task further enhances the stress response [37].…”
Section: Methodsmentioning
confidence: 99%
“…More contradictory are the data reported in the few studies which have investigated the repeatability of heart autonomic responses, induced either by the cold pressor test (Fasano et al, 1996;Jaurequi-Renaud et al, 2001) or by other non-painful procedures, like the tilt test (Cloarec-Blanchard et al, 1997) and the Valsalva maneuver (Lawrence et al, 1992). In this case, the findings are contrasting and not conclusive, probably because different models have been tested.…”
Section: Discussionmentioning
confidence: 86%
“…For instance, pain threshold appears to be lowered by situations inducing anxiety or augmented by situations provoking fear, as occurs in the stress response (Rhudy and Meagher, 2000). The repeatability of autonomic responses to pain, however, has been addressed with contrasting results (Fasano et al, 1996;Jaurequi-Renaud et al, 2001). The autonomic nervous system is greatly influenced by painful stimulation (Janig, 1995).…”
Section: Introductionmentioning
confidence: 99%